Threshold behavior of optimal safety stock coverage in the presence of extended production disruptions. (4th December 2019) - Strohhecker, Jürgen; Größler, Andreas
Abstract : Purpose: The purpose of this paper is to investigate the effects of extended production disruptions because of process quality breakdowns on operational and financial performance. The investigation is conducted over the market cycle of a highly profitable product, e.g. a patented pharmaceutical. In particular, the study evaluates performance effects of different inventory level policies. The paper considers different degrees of availability of a substitute product. Design/methodology/approach: The study uses simulation experiments based on system dynamics methodology to derive inventory policies on handling infrequently happening but severe production process breakdowns. The simulation model is inspired by empirical case study research and is based on standard modeling formulations from the literature. Findings: The scenario analyses show that the optimal level of safety stock coverage time depends in a highly non-linear manner on various economic parameters and shows threshold behavior. Research limitations/implications: In subsequent studies, the effect of the degree of backlogging and the effect of the repeated occurrence of quality breakdowns on the results can be investigated. Practical implications: The critical importance of safety stock and its non-linear relationship to economic product characteristics is emphasized. Originality/value: Motivated by a real-world case study, the paper uses standard model formulations to derive insights for a specific business situation after considering uncertainty in the environment.